Advertisements
Advertisements
Question
If 2( x2 + 1 ) = 5x, find :
(i) `x - 1/x`
(ii) `x^3 - 1/x^3`
Solution
(i) 2( x2 + 1 ) = 5x
( x2 + 1 ) = `5/2`x
Dividing by x, we have
`( x^2 + 1 )/x = 5/2`
⇒ `( x + 1/x ) = 5/2` .....(1)
Now consider the expansion of `( x + 1/x )^2` :
`( x + 1/x )^2 = x^2 + 1/x^2 + 2`
⇒ `(5/2)^2 = x^2 + 1/x^2 + 2` [From(1)]
⇒ `(5/2)^2 - 2 = x^2 + 1/x^2`
⇒ `25/4 - 2 = x^2 + 1/x^2`
⇒ `x^2 + 1/x^2 = [25 - 8 ]/4`
⇒ `x^2 + 1/x^2 = 17/4` ....(2)
Now consider the expansion of `( x - 1/x )^2` :
`( x - 1/x )^2 = x^2 + 1/x^2 - 2`
⇒ `( x - 1/x )^2 = 17/4 - 2` [from(2)]
⇒ `( x - 1/x )^2 = [ 17 - 8]/4`
⇒ `( x - 1/x )^2 = 9/4`
⇒ `( x - 1/x )^2 = +- 3/2` ....(3)
(ii) We know that,
`( x^3 - 1/x^3 ) = ( x - 1/x )^3 + 3( x - 1/x )`
∴ `( x^3 - 1/x^3 ) = ( +- 3/2 )^3 + 3(+- 3/2)` [from(3)]
= `+- 27/8 + 9/2`
⇒ `( x^3 - 1/x^3 ) = +- [27 + 36]/8`
⇒ `( x^3 - 1/x^3 ) = +- 63/8`